Cyclin-dependent kinase inhibitors: efficacy and safety - I. B. Kononenko; A. V. Snegovoi; V. Yu. Selchuk (Медицинский совет, 2019)
Breast Cancer is the most common type of cancer worldwide. Scientific advances and new ways of treating have significantly improved the prognosis of breast cancer in recent decades. The emergence of modern cyclin-dependent kinase (CDK) inhibitors has changed the treatment paradigm for metastatic hormone receptor (HR)-positive breast cancer. In the past four years, the CDK4/6 inhibitors, ribociclib, palbociclib and abemaciclib, received their first FDA approval for the treatment of Hormone Receptor (HR)- positive and Human Epidermal growth factor Receptor 2 (HER2)-negative breast cancer after showing significant improvements in progression-free survival in the PALOMA, MONALEESA and the MONARCH randomized clinical trials, respectively. In the Russian standards for the treatment of metastatic HR positive and HER2-negative breast cancer are included two inhibitors of CDK4/6 – ribociclib, palbociclib. This review summarizes the background of clinical efficacy and potential toxicities seen with the use CDK4/6 inhibitors with endocrine treatment in pre- or postmenopausal women with hormone receptor–positive, HER2-negative advanced or metastatic breast cancer. Despite the similar toxicities, inhibitors of cyclin-dependent kinases differ in their severity and some types of adverse events. Most hematologic abnormalities seen with CDK4/6 inhibitors are not complicated and are adequately managed with standard supportive care and dose adjustments when indicated. This review focuses on the practical management of adverse events associated with CDK4/6 inhibitors.